Optimization of Sol–Gel Catalysts with Zirconium and Tungsten Additives for Enhanced CF4 Decomposition Performance - Younghee Jang; Sang Moon Lee; Sung Su Kim; D. Duc Nguyen (Molecules)
This study investigated the development and optimization of sol–gel synthesized Ni/ZrO2-Al2O3 catalysts, aiming to enhance the decomposition efficiency of CF4, a potent greenhouse gas. The research focused on improving catalytic performance at temperatures below 700 °C by incorporating zirconium and tungsten as co-catalysts. Comprehensive characterization techniques including XRD, BET, FTIR, and XPS were employed to elucidate the structural and chemical properties contributing to the catalyst’s activity and durability. Various synthesis ratios, heat treatment temperatures, and co-catalyst addition positions were explored to identify the optimal conditions for CF4 decomposition. The catalyst composition with 7.5 wt% ZrO2 and 3 wt% WO3 on Al2O3 (3W-S3) achieved over 99% CF4 decomposition efficiency at 550 °C. The study revealed that the appropriate incorporation of ZrO2 enhanced the specific surface area and prevented sintering, while the addition of tungsten further improved the distribution of active sites. These findings offer valuable insights into the design of more efficient catalysts for environmental applications, particularly in mitigating emissions from semiconductor manufacturing processes.